2018
DOI: 10.22161/ijeab/3.3.43
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Some Heavy Metals in Selected Dumpsites in Ozoro, South-South, Nigeria

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
3
2
Order By: Relevance
“…Agbeshie [1] reported that the iron, cadmium and lead concentrations of soil samples collected from a dumpsite in Ghana, were higher than the concentrations recorded in the control soil sample. The differences observed in the soil heavy metals concentrations between our results and other studies results [1,20], could be attributed to the sampling period, to the age of the dumpsite, transport mechanisms, remediation potential of the natural vegetation, locations at which the soil samples were sampled and organic materials present in the sampling location. Studies [42][43][44] showed that many plant species and organic materials (microbial decomposition) have significantly impacts on the remediation of the heavy metals content in the soil, thus lowering the heavy metals accumulation in the soil.…”
Section: Heavy Metals Concentrationscontrasting
confidence: 91%
See 3 more Smart Citations
“…Agbeshie [1] reported that the iron, cadmium and lead concentrations of soil samples collected from a dumpsite in Ghana, were higher than the concentrations recorded in the control soil sample. The differences observed in the soil heavy metals concentrations between our results and other studies results [1,20], could be attributed to the sampling period, to the age of the dumpsite, transport mechanisms, remediation potential of the natural vegetation, locations at which the soil samples were sampled and organic materials present in the sampling location. Studies [42][43][44] showed that many plant species and organic materials (microbial decomposition) have significantly impacts on the remediation of the heavy metals content in the soil, thus lowering the heavy metals accumulation in the soil.…”
Section: Heavy Metals Concentrationscontrasting
confidence: 91%
“…Additionally, the higher heavy metals concentrations recorded in this study compared to previous results of [20], signified that heavy metals is accumulating in the area at a faster rate, hence approaching its heavy metals contamination threshold. Therefore, there is an urgency of relocating it from its present location, since it is located within residential area, to prevent heavy metals related ailments.…”
Section: Heavy Metals Concentrationscontrasting
confidence: 42%
See 2 more Smart Citations
“…Heavy metals bioavailability in soils to a great degree depends on their spread between the solid and solution phases (Wang b et al 2021; Xu et al, 2022). This spreading is sequentially reliant on the soil processes such as; specific adsorption, cation exchange, precipitation as well as complexation (Liu et al, 2018;Ojebah and Uwague, 2018;Petruzzelli et al, 2020). pH is commonly known to be the very significant factor affecting metal bioavailability in soils, with solubility and pH more often than not displaying an inverse correlation with metal bioavailability (Petruzzelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%